REALISING HUMAN RIGHTS IN TIMES OF RECESSION: WHAT COULD IRELAND HAVE DONE DIFFERENTLY? - Higgins, Noelle (Teisė, 2015)
This article addresses the impact of recession on human rights in Ireland. It illustrates how the current legal framework for the protection of economic, social and cultural rights needs to be strengthened and how a human rights impact assessment of budgetary decisions is necessary in order to ensure better protection of rights for those affected by recession in the future.